2022
DOI: 10.1002/er.7985
|View full text |Cite
|
Sign up to set email alerts
|

Anodic dissolution behavior of Zr‐Dy alloy in LiCl‐KCl molten salt

Abstract: To research Zr-Dy alloy dissolution behavior at anode, the electrode process of LiCl-KCl-K 2 ZrF 6 -DyCl 3 on an inert W electrode was firstly explored through a group of electrochemical techniques. The depolarization phenomenon was observed owing to the formation of Zr-Dy solid solution, and the redox potentials of Dy(III)/Dy, Zr(II)/Zr-Dy solid solution, Zr(IV)/Zr(II) and Zr(II)/Zr (0) were determined. Then, Zr and Zr-Dy alloy dissolution behaviors at anode were explored by cyclic voltammetry and linear swee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Sakamura 7 employed Zr metal as the working electrode in a cyclic-voltammetry (CV) analysis and found that Zr undergoes a passivation process during anodic dissolution. Ghosh et al 21 and Han et al 19 advanced similar suggestions. Koyama et al 22 and Iizuka et al 23 pointed out that the anodic dissolution of a Zr-rich alloy leaves a dense salt layer on the alloy surface.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Sakamura 7 employed Zr metal as the working electrode in a cyclic-voltammetry (CV) analysis and found that Zr undergoes a passivation process during anodic dissolution. Ghosh et al 21 and Han et al 19 advanced similar suggestions. Koyama et al 22 and Iizuka et al 23 pointed out that the anodic dissolution of a Zr-rich alloy leaves a dense salt layer on the alloy surface.…”
Section: Introductionmentioning
confidence: 70%
“…One promising methodology for recycling spent fuel Zralloy cladding is an electrometallurgical process that uses molten LiCl-KCl salt as a medium. [7][8][9][10][11][12][13][14][15][16][17][18][19] For such a process, the direct anodic dissolution of Zr-alloy cladding is the most straightforward strategy for administering Zr reactants into molten LiCl-KCl salts. 8,16 Since Zr-alloy cladding is generally composed of 97% or more of Zr; 8 it is essential to rigorously understand the anodic dissolution behavior of Zr in molten LiCl-KCl salt.…”
Section: Introductionmentioning
confidence: 99%
“…Evidently, the initial dissolution potential, rapid dissolution potential, and passivation potential of UC 0.4 O 0.6 were observed at −0.14, 0.27, and 1.25 V, respectively. 19,20 With the increase of cycle times, the initial dissolution potential of UC 0.4 O 0.6 remained basically unchanged, while the dissolution current intensity continuously increased, indicating that the electrode area of the UC 0.4 O 0.6 anode was continuously changing.…”
Section: Resultsmentioning
confidence: 97%